Aberrant expression of AID and AID activators of NF-κB and PAX5 is irrelevant to EBV-associated gastric cancers, but is associated with carcinogenesis in certain EBV-non-associated gastric cancers - Mohri, Takashi (Oncol Lett, 2017)
Epstein-Barr virus-associated gastric carcinoma (EBVaGC) is a distinct subtype of gastric cancer characterized by clinicopathological features including lymphoepithelioma-like histology. Aberrant expression of activation-induced cytidine deaminase (AID) as a genomic modulator was demonstrated through pathogen-related nuclear factor κB (NF-κB) signaling in Helicobacter pylori-associated gastric cancer. To elucidate whether or not AID expression is relevant to carcinogenesis in EBVaGC, immunohistochemical expression of AID and AID-regulatory factors between EBVaGC and EBV-non-associated gastric carcinoma (GC) were evaluated, each using 15 cases of GC with lymphoid stroma (GCLS) and other types of GC. Aberrant expression of AID, NF-κB and paired box 5 (PAX5) were significantly decreased in EBVaGC (0/11, 1/11 and 1/11) compared with in EBV-non-associated GC (7/19, 12/19 and 11/19) (P=0.025, 0.005 and 0.01, respectively); however, no significant difference in c-Myb proto-oncogene expression was identified. AID expression was also decreased in EBV-associated GCLS (0/10) compared with in EBV-non-associated GCLS (3/5). Unexpectedly, decreased expression of NF-κB and PAX5 was observed in GCLS (1/15 and 2/15) compared with in GC without LS (12/15 and 10/15) (P<0.001 and P=0.003, respectively). Decreased AID expression observed in EBVaGC is consistent with the reported molecular characterization of hypermethylation and rare somatic gene mutation in EBVaGC. Only PAX5 was identified to be significantly associated with venous invasion (P=0.022). The results of the present study suggest that pathogen-induced AID expression may be irrelevant to carcinogenesis of EBVaGC, whereas it contributes to carcinogenesis in certain types of EBV-non-associated GC.